AI between threat and benefactor for the competences of the human working force - Olimpia Ban; Irina Maiorescu; Mihaela Bucur; Gabriel Cristian Sabou; Betty Cohen Tzedec (Amfiteatru Economic, 2024)
The fast pace of the inclusion of AI in almost all sectors of human activity, with more and more accurate and effective results, transforms society at all levels. Changes have already been noticed in the structure of jobs offers for human tasks, since AI provides skills that can successfully replace human competencies in certain areas of activity. Hence, our paper aimed to investigate whether AI is perceived as a threat or a benefactor for the competencies of the human workforce. The analysis of the relevant scientific literature was followed by a quantitative investigation on 512 adult persons of all ages, sex, and having various work experiences. Research results indicate that job losses, dehumanisation of the work, as well as lower intellectual capacity and skills for humans that are no longer used to solve problems and work tasks on their own, are the main threats brought by AI. At the same time, there are perceived AI benefits, such as rapidity in solving some work tasks and reducing the physical and mental strain of employees. In general, it can be said that younger generations, who also have less work experience, are more open to using the AI competencies to solve their work tasks.
Keywords: F10; J62; O32; O52; 330; AI threats; AI benefits; competencies; human workforce; workplace